Viruses, microsporidia and glyphosate residues in Africanized honey bees Apis mellifera, under field conditions - Guimarães-Cestaro, Lubiane; Serrão, José Eduardo; Martins, Marta Fonseca; Martínez, Luis Carlos; Alves, Maria Luisa Teles Marques Florêncio; Lazzarini, Karina Rosa Guidugli; Nocelli, Roberta Cornélio Ferreira; Malaspina, Osmar [UNESP]; Evans, Jay Daniel; Teixeira, Érica Weinstein (Taylor & Francis, 2024)
Bees are affected by several factors, including pathogens and pesticides, which may cause mortality and consequent population decline. Considering the ecological and economic importance of these pollinators, this study evaluated the occurrence of the microsporidia Nosema apis and Nosema ceranae, the viruses ABVP, DWV, BQCV, KBV, IAPV and CBPV and residues of the pesticides atrazine, chlorantraniliprole, deltamethrin, fipronil and glyphosate in workers from field colonies of Africanized honey bee Apis mellifera across one year. The presence of pesticide residues was also evaluated in honey and pollen samples. All tested viruses were found in the workers, with BQCV showing the highest copy number. BQCV levels were correlated with relative humidity. Nosema ceranae was the only microsporidian with higher intensities of infection during summer and autumn; seasons with high availability of food resources, which can act as dispersers of this pathogen. Small amounts of glyphosate and its metabolite were detected in the bees tested. These data show that honey bees are contaminated with pathogens and pesticides in the field and present correlative data for these threats.
Keywords: Black queen cell virus; honey bee; Nosemasp; pathogens; pesticides